Internalisasi Nilai-Nilai Etika Kristen dalam Pembelajaran Pendidikan Agama Kristen - Operahmat Halawa (Sekolah Tinggi Teologi SAPPI Ciranjang, 2026)
This study analyzes the role of Christian Religious Education teachers in internalizing Christian ethical values among eighth-grade students at SMP Negeri 03 Sogaeadu. A descriptive qualitative approach was employed, with data collected through observations, interviews, and documentation. The participants consisted of Christian Religious Education teachers, the principal, and students. Data were analyzed inductively through data reduction, data display, and conclusion drawing. The findings reveal that teachers play a significant role in internalizing Christian ethical values through role modeling, habituation, guidance, and contextual learning. However, the effectiveness of this process is constrained by instruction that remains content-oriented, inconsistent teacher role modeling, the influence of digital technology and peer environments, and limited collaboration between schools and families. The study concludes that successful internalization of Christian ethical values requires the synergy of teachers, schools, families, and the broader social environment to foster students' holistic character development.